Development of digital products and services: Proposal of a framework to analyze versioning actions. Issue 5 (October 2016) - De Sordi, José Osvaldo; Nelson, Reed, Elliot; Meireles, Manuel; da Silveira, Marco Antonio
Abstract: Recent expansion in availability of data and of technological resources, as well as the ease of generating, reproducing and adapting digital products and services (DPS), has greatly expanded our ability to quickly generate a wide range of digital offerings. This increased capacity and complexity in turn demands greater operational and managerial effectiveness of organizations regarding the management of DPS versions and of versioning practices. Although versioning has been the subject of study in many disciplines, there is yet little theory development that explicitly seeks to understand the impact and dynamics of versioning actions. Using grounded theory as a research method, we develop a broad framework for conceptualizing versioning actions with the aim of obtaining better understanding of different versioning strategies and of the impact of versioning actions on DPS quality, taken from the interference analysis of the dimensions of information quality related to the DPS. Our framework encompasses actions directed to the three principal components of the DPS architecture, namely the content, technological and process platform, as well as their subcomponents. The framework aims to help researchers and managers reflect on and select the most effective versioning actions, thus reducing the incidence of unexpected events arising from interdependence among the dimensions of information quality that may otherwise be missed during the planning and definition of the versioning actions.